2022
DOI: 10.4317/medoral.25042
|View full text |Cite
|
Sign up to set email alerts
|

What is the accuracy of the surgical guide in the planning of orthognathic surgeries? A systematic review

Abstract: Background To investigate the true accuracy of the surgical guide in the planning of orthognathic surgeries, which are performed worldwide. Material and Methods A systematic search was conducted in the PubMed database, Web of science, Scopus and Embase, covering August 2020 to January 2021. Studies that included patients with dentofacial deformity including anteroposterior, vertical and asymmetry problems who were undergoing an orthognathic surgery procedure were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(59 reference statements)
0
2
0
2
Order By: Relevance
“…In a 2022 systematic review of orthognathic surgeries, surgical guides were found to be highly precise and accurate, with low error values represented by the CAD/CAM technique. 19 VSP and 3D-printed guides have also been used as a volumetric assessment tool for soft tissue correction with fat grafting in facial asymmetry. 20 While intraoperative navigation in facial allotransplantation can be useful in surgical accuracy, one disadvantage is the lack of precision of osteotomies compared with 3Dprinted guides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a 2022 systematic review of orthognathic surgeries, surgical guides were found to be highly precise and accurate, with low error values represented by the CAD/CAM technique. 19 VSP and 3D-printed guides have also been used as a volumetric assessment tool for soft tissue correction with fat grafting in facial asymmetry. 20 While intraoperative navigation in facial allotransplantation can be useful in surgical accuracy, one disadvantage is the lack of precision of osteotomies compared with 3Dprinted guides.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2022 systematic review of orthognathic surgeries, surgical guides were found to be highly precise and accurate, with low error values represented by the CAD/CAM technique. 19 VSP and 3D-printed guides have also been used as a volumetric assessment tool for soft tissue correction with fat grafting in facial asymmetry. 20…”
Section: Discussionmentioning
confidence: 99%
“…Também são necessários exames de imagem como radiografia panorâmica e cefalométrica, nos quais são feitos os traçados preditivos, em que é definido quais movimentos serão utilizados na cirurgia, é necessário o uso de modelos dentários de gesso, que são fixados a um articulador dentário. A simulação cirúrgica é finalizada movendo os traçados ósseos para a posição desejada (GOULART et al, 2022).…”
Section: Planejamento Cirúrgico Convencionalunclassified
“…Revisão de Literatura caso o paciente não esteja nos posicionamentos ideais durante a aquisição das imagens ou na análise cefalométrica, o que também pode resultar em falhas técnicas(GOULART et al, 2022). Revisão de Literatura necessidade do uso de arco facial, pois utiliza imagens tridimensionais, que permitem a visualização de estruturas adjacentes e sua influência na oclusão(GOULART et al, 2022).…”
unclassified